Tacky's Revolt: The Story of an Atlantic Slave War - Sorrell III, Clifton E. (Labour / Le Travail, 2022)
The article reviews the book, "Tacky's Revolt: The Story of an Atlantic Slave War," by Vincent Brown.
Keywords: BROWN; Vincent; NONFICTION; SLAVE insurrections; TACKY'S Revolt: The Story of an Atlantic Slave War (Book)